An Experimental Study Into the Effects of Cumulative Energy Damage on the Mechanical Properties of Coal - Guo, Shuai; Huang, Peng; Spearing, A.J.S. (Sam); Wang, Zhaojun; Dong, Xiangjian (Frontiers in Materials, 2021)
The accumulated damage of the surrounding rocks induced by the existing coal mining activities (such as excavation and extraction) is the initial mechanical background of the rock and coal for the further mining operations. An energy-based Cumulative Initial Damage (CID) variable was proposed to account for such existing damage. With the MTS815 electro-hydraulic servo-controlled system, coal samples with different CID value were prepared by cyclic pre-loading and unloading process, and a novel experimental framework was presented to investigate the effect of CID on the further mechanical properties of the CID coal samples.. The deformation characteristics, peak strength, peak strain, dilatancy characteristics, brittle-ductile transformation behavior, and microscopic structure of the CID coal samples were investigated in detail. The triaxial compression tests showed that with the increased of CID value, the compaction part of the coal samples was shorter and the strain softening stage became longer. When the CID value was increased from 0 to 0.521, the deviation stress and peak strain of the coal decreased by 31.4% and 37.7%, respectively and the main characteristic of the fracture morphology changed from cleavage steps to dimpling.